THE IMPACT OF TEACHER ACCENT AND SPEECH CLARITY ON STUDENT COMPREHENSION (American Journal of Research in Humanities and Social Sciences, 2025)
In today’s increasingly globalized classrooms, English language learners are exposed to a wide range of teacher accents and speech patterns. This study investigates how a teacher’s accent and speech clarity affect students’ comprehension in English as a Foreign Language (EFL) setting. Drawing on qualitative and quantitative data collected from secondary school learners and language instructors; the research explores learners’ ability to understand instructional content delivered in various native and non-native English accents. The findings indicate that while exposure to different accents can improve listening flexibility over time, unfamiliar or heavily accented speech especially when combined with poor articulation can hinder comprehension, reduce learner confidence, and negatively impact academic performance.